Synchronous atrioventricular sequential pacing utilizing conventional and leadless pacemakers in an elderly patient: a case report. Issue 1 (12th December 2022) - Bodagh, Neil; Cheng, Kevin; Eysenck, William; Wong, Tom
Abstract: Background: Leadless pacemakers present a viable alternative to conventional transvenous devices to mitigate the risk of lead- and/or pocket-related complications. In elderly patients who have encountered ventricular lead failures with transvenous pacemakers, this option may enable the delivery of atrioventricular synchronous pacing therapy, while obviating the requirement for lead extraction and lead-based pacemaker re-implantation. Case summary: This case report describes the successful implantation of a leadless pacemaker in a 90-year-old who had undergone two dual-chamber permanent pacemaker implantation procedures with a failure of three of four previously implanted leads. Atrioventricular synchronous pacing was achieved, as the leadless device was able to track the atrial-paced rhythm from the pre-existing right-sided device. Discussion: In elderly patients who have encountered issues with transvenous pacemakers, alternative approaches should be considered to mitigate the risk of future complications. Leadless pacemakers may offer a low-risk solution, enabling the delivery of atrioventricular synchronous pacing therapy in such patient groups. Future studies should be designed to delineate whether these devices could be utilized as a first-line approach in certain situations.